2019
DOI: 10.1186/s12906-019-2613-6
|View full text |Cite
|
Sign up to set email alerts
|

Xiaoyaosan exerts antidepressant-like effects by regulating the functions of astrocytes and EAATs in the prefrontal cortex of mice

Abstract: Background Mounting evidence indicates that the cerebral cortex is an important physiological system of emotional activity, and its dysfunction may be the main cause of stress. Glutamate is the primary excitatory neurotransmitter in the central nervous system (CNS), which initiates rapid signal transmission in the synapse before its reuptake into the surrounding glia, specifically astrocytes (ASTs). The astrocytic excitatory amino acid transporters 1 (EAAT1) and 2 (EAAT2) are the major transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…It has been demonstrated that Xiaoyaosan can decrease the Hamilton Depression Rating Scale (HAMD) and Self-Rating Depression Scale (SDS) scores in depression patients (Feng et al, 2014;Feng et al, 2016). Xiaoyaosan has been demonstrated to ameliorate chronic unpredictable mild stress (CUMS)-induced depression-like behaviors (Liu et al, 2019) and promote neuronal plasticity in HT22 cells. Xiaoyaosan can protect against corticosterone-induced stress injury in primary hippocampal neurons (PHNs) (Cao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that Xiaoyaosan can decrease the Hamilton Depression Rating Scale (HAMD) and Self-Rating Depression Scale (SDS) scores in depression patients (Feng et al, 2014;Feng et al, 2016). Xiaoyaosan has been demonstrated to ameliorate chronic unpredictable mild stress (CUMS)-induced depression-like behaviors (Liu et al, 2019) and promote neuronal plasticity in HT22 cells. Xiaoyaosan can protect against corticosterone-induced stress injury in primary hippocampal neurons (PHNs) (Cao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CUMS procedure followed during treatment. The dosage of Flu and Bup obtained from previous studies (Yi et al, 2013) and the volume of concentration and volume of the gavage administration of Psycodigest determined based on human and mouse dose conversion formula (Liu et al 2019).…”
Section: Drugs and Administrationmentioning
confidence: 99%
“…and the volume of concentration and volume of the gavage administration of Psycodigest determined based on human and mouse dose conversion formula(Liu et al 2019). Behavioral testThe sucrose preference test (SPT)At the end of treatment, the Sucrose preference test was performed as described previously(Mao et al, 2009).…”
mentioning
confidence: 99%
“…The Xiaoyaosan dry powder and the fluoxetine capsules were dissolved in distilled water, then the mice in the two treatment groups received Xiaoyaosan (0.254 g/kg/d) and fluoxetine (2.6 mg/kg/d) by intragastric administration after the daily CUMS procedure, respectively. 30 Meanwhile, mice in the control and CUMS group received 0.5 mL physiological saline.…”
Section: Methodsmentioning
confidence: 99%